Meningioma in the third trimester of pregnancy: A case report - Carla Ettore; Elisa Zambrotta; Ferdinando Antonio Gulino; Giosuè Giordano Incognito; Francesco Giuseppe Cannone; Giuseppe Ettore (Elsevier, 2023)
Meningiomas are rare benign tumors during pregnancy. They can put both the mother and the fetus at risk because rapid changes in size may occur. The study reports a case of olfactory groove meningioma in a 34-year-old pregnant woman with visual impairment, anosmia, and dysgeusia that increased in severity during the 29th week of gestation. Magnetic resonance imaging showed an olfactory groove meningioma. The patient underwent a preterm cesarean section to avoid the worsening of the clinical condition due to intracranial compression phenomena. A computed tomography scan of the brain supported the diagnosis. The surgical intervention occurred on the third day after delivery. The clinical course was uneventful and the chiasmal syndrome improved in the following 2 months. Meningiomas in pregnancy may present unique challenges and have a wide array of clinical presentations. Management of maternal meningiomas can be complex and requires a multidisciplinary approach. The treatment decision largely depends on the size and location of the tumor, the presence of symptoms, gestational age, and fetal well-being. Further research is needed to enhance the understanding of the underlying mechanisms and improve management approaches for this rare condition.